Peran Pendidik dalam Penerapan Internet Sehat Menurut Islam - Saefulloh, Ahmad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
The purpose of this study is to find out the role of educators in applying healthy internet use according to Islam. This study used descriptive qualitative method with phenomenalogy analysis involving several family members. Data collection through snowball sampling technique to get saturated data. The results of this study that preventive steps that can be done by educators and parents so that students can implement healthy internet use according to Islam is by following the roles and duties of the Prophet Muhammad in educating, educating and parents also need to know the use of the internet and do some preventive tricks such as conducting assistance, carrying out the 1821 movement, and conducting educative supervision of children's internet use. So that children activities can be controlled well.